Efek Citra Toko terhadap minat Beli Konsumen pada Brastagi Supermarket Gatot Subroto Medan melalui Persepsi Nilai dan Kesadaran Merek - Stephen Simon; Ronald Ronald; Amelia Amelia (Journal of Management and Bussines (JOMB), 2024)
The aim of the research is to analyze the effect of store image on consumer buying interest at Brastagi Supermarket Gatot Subroto Medan through perceived value and brand awareness. The data collection technique in this research used an electronic Google Form questionnaire from 135 respondents who had shopped at Brastagi Supermarket Gatot Subroto Medan. This research uses Smart Partial Least Squares Analysis (SmartPLS). The research results show that price, consumer service, trade products and architecture have a significant effect on store image. Apart from that, this research also shows that store image has a significant positive effect on consumer buying interest through perceived value and brand awareness. The conclusion is that retail businesses, especially supermarkets, must consider these variables if they want to increase consumer buying interest. Keywords: Architecture, Price, Customer Service, Trade Products